2020
DOI: 10.3390/s20113012
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PPP-RTK Performance Analysis Using Ionospheric Corrections from Multi-Scale Network Configurations

Abstract: The long convergence time required to achieve high-precision position solutions with integer ambiguity resolution-enabled precise point positioning (PPP-RTK) is driven by the presence of ionospheric delays. When precise real-time ionospheric information is available and properly applied, it can strengthen the underlying model and substantially reduce the time required to achieve centimeter-level accuracy. In this study, we present and analyze the real-time PPP-RTK user performance using ionospheric corrections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…In other words, Equation (2) is the so-called ionosphere-float model. However, one can easily augment Equation (2) with the external ionospheric delay corrections by making use of precise network-derived slant ionospheric corrections on the basis of the best linear unbiased prediction method [53]. It needs to be noted that satellite and receiver differential code biases (DCB) are lumped into the estimable ionospheric delay; therefore, one must carefully take into account the DCBs when implementing the external ionospheric delay corrections into the PPP-RTK model to ensure the absence of biases in the functional model of the ionosphere-corrected PPP-RTK user.…”
Section: Ppp-rtk Modelmentioning
confidence: 99%
“…In other words, Equation (2) is the so-called ionosphere-float model. However, one can easily augment Equation (2) with the external ionospheric delay corrections by making use of precise network-derived slant ionospheric corrections on the basis of the best linear unbiased prediction method [53]. It needs to be noted that satellite and receiver differential code biases (DCB) are lumped into the estimable ionospheric delay; therefore, one must carefully take into account the DCBs when implementing the external ionospheric delay corrections into the PPP-RTK model to ensure the absence of biases in the functional model of the ionosphere-corrected PPP-RTK user.…”
Section: Ppp-rtk Modelmentioning
confidence: 99%
“…Since the advent of PPP-RTK, efforts have been made to achieve fast (i.e., instantaneous or near-instantaneous) centimeter-level accuracy. Applying precise ionospheric corrections from regional networks with a station spacing of a few hundreds of kilometers has been shown to provide almost-instantaneous positioning solutions based on GPS dual-frequency data [2,[4][5][6]. The establishment of such dense networks, however, is not highly attractive because of the cost and complex operation requirements involved, and is also difficult or even impossible in certain areas.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that centimetre-level positioning accuracy can be achieved based on GPS-or BDS-only observations, and performance can be further improved by realizing PPP AR method. Psychas et al (2020) analysed the real-time PPP-RTK user performance using ionospheric corrections from multi-scale regional networks during a day with medium ionospheric disturbance. Results showed that sub-10 cm horizontal accuracy can be achieved within 1 min and 2 min based on corrections from a network with 68 km and 115 km spacing.…”
Section: Introductionmentioning
confidence: 99%